The Phenomenology of Career Sustainability on Teachers from Millennial Generation. - Dian Purnamasari; Didik Junaidi Rachbini; Niko Sudibjo; Evo Sampetua Hariandja (Universitas Muhammadiyah Enrekang, 2023)
Sustainability career for teachers has not been a concern due to the assumption teaching will always be a sustainable career. Data from UNESCO stated that to achieve the 2023 Education goals, the world needs almost 69 million new teachers. The article analyzes teacher career sustainability using the Phenomenology methods to get the perspective of Millennial Generation teachers specifically from schools based on Islamic religion on the sustainability careers of the teachers. Method of data gathered using interviews and observation for 3 years starting from 2020-2023. The interview research is broken down into word codes which resulting in these keywords that affect teachers' career sustainability in Millennial Generation teachers who work in Islamic religion school base (mostly Muhammadiyah): Teachers Motivation, Teacher Commitment, Principals Leadership, Teacher Perspective of workload, and internalization of Islamic Values in the Teachers From the interview result, the internalization of Islamic values holds a deep impact on increasing the sustainability career of teachers who hold Islam as their religion and work in Islamic schools.